Logistics development study of east coast region: early investigation - Zuraimi Abdul Aziz; Mohd Rafi Yaacob; Mohamed Dahlan Ibrahim (2012)
Logistics industry is one of the catalysts for the development of industrialisation in Malaysia which is linked to the international trade. The performance of the industry will have an impact of the progress of the nation’s industrialisation and its competitiveness in international trade. The development of logistics management has facilitated production and distribution processes and created more access to the global market. It is within this competitive environment that shippers and consignees require efficient logistics services to move their goods at the right place, at the right time, in the right quantity, conditions and at the right price. Logistics development is paramount important to the country in supporting economic and growth and enhancing competitiveness. Malaysia as well as many developing countries are still at the moderate stage in developing logistics system and often face considerable challenges and constraints to provide efficient and effective logistics services. Therefore, the research objectives (i) to examine the current logistics infrastructures in the East Coast Region of Peninsular Malaysia, (ii) to find out the constraints and challenges in logistics development and (iii) to identify the capability of logistics service providers in providing the services. To achieve the objectives of this research, interviews were conducted with selected local authority, manufacturer, port operator and logistics service provider in this region to achieve the objectives of this research. The overall findings show that the existing logistics infrastructures are not well occupied the logistics development in the region. Amongst the constraints and challenges were mind setting of the communities and financial issues in organization. However, at the time beings, most respondents were satisfied with the services rendered by logistics service providers.